Business structures in the international innovation economy - Cherepanova, V. O.; Gliznutsa, M. Yu.; Pererva, P. G. (Видавничий дім "Києво-Могилянська академія", 2023)
It has been proven that the knowledge economy turns into a powerful impetus for socio-economic development, increases the competitiveness of products, contributes to the diversification of activities, helps to raise production in the regions and the country as a whole.
Підприємницькі структури в міжнародній інноваційній економіці
Keywords: business structures; innovative activity; economy; intellectual property; production; efficiency